1996
DOI: 10.1007/bf02109905
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of matrix Ca2+ content by the ADP/ATP carrier in brown adipose tissue mitochondria. Influence of membrane lipid composition

Abstract: The role of the adenine nucleotide translocase on Ca2+ homeostasis in mitochondria from brown adipose tissue was examined. It was found that in mitochondria incubated with 50 microM Ca2+, ADP was not needed to retain the cation, but it was required for strengthening the inhibitory effect of cyclosporin on membrane permeability transition as induced by menadione. In addition, carboxyatractyloside was unable to promote matrix Ca2+ release, even though it inhibits the ADP exchange reaction. However, when the Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Carboxyatractylate (CAT) (Figures 1, 4 and 5) and bongkrekate (BKA) (Figure 9), potent and highly specific inhibitors of ANT (Klingenberg, 1975), strongly inhibited uncoupling induced by hydroxynonenal in mitochondria from kidney, liver, heart and skeletal muscle. ANT is present in BAT mitochondria at about the same concentration as it is in liver mitochondria (Chavez et al ., 1996), and in BAT mitochondria (Figure 6) carboxyatractylate inhibited hydroxynonenal‐induced uncoupling by about the same absolute extent as it did in liver mitochondria (Figure 4A). However, because of the high UCP1 concentration in BAT mitochondria, the percentage inhibition by carboxyatractylate was much less than it was in mitochondria from the other tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Carboxyatractylate (CAT) (Figures 1, 4 and 5) and bongkrekate (BKA) (Figure 9), potent and highly specific inhibitors of ANT (Klingenberg, 1975), strongly inhibited uncoupling induced by hydroxynonenal in mitochondria from kidney, liver, heart and skeletal muscle. ANT is present in BAT mitochondria at about the same concentration as it is in liver mitochondria (Chavez et al ., 1996), and in BAT mitochondria (Figure 6) carboxyatractylate inhibited hydroxynonenal‐induced uncoupling by about the same absolute extent as it did in liver mitochondria (Figure 4A). However, because of the high UCP1 concentration in BAT mitochondria, the percentage inhibition by carboxyatractylate was much less than it was in mitochondria from the other tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiolipin may modulate apoptotic processes by inhibiting MPT. In fact, it provides an increased pool of negative ions that nonspecifically bind Ca 2+ , thereby preventing it from binding to protein sites that induce the opening of mitochondrial pores 45. Lieser et al46 found that mitochondrial cardiolipin content increased 10 days after BDL and thus protected against cell death by increasing the threshold for MPT.…”
Section: Discussionmentioning
confidence: 99%
“…These values correlated with a diminution in ANT levels, from 58 nmol/mg in control rats to 40 nmol/mg in hypothyroid rats. In addition to its normal function, ANT forms the inner membrane channel of the mitochondrial permeability transition pore (MPTP) [1315] which allows the movement of matrix ions and metabolites through the mitochondrial membrane (Figure 1). Binding of cyclophilin-D (CyP-D) to ANT matrix surface facilitates a calcium-triggered conformational change converting it from a specific transporter to a nonspecific pore.…”
Section: Hypothyroidism and Mitochondriamentioning
confidence: 99%
“…Binding of cyclophilin-D (CyP-D) to ANT matrix surface facilitates a calcium-triggered conformational change converting it from a specific transporter to a nonspecific pore. Both proteins along with the voltage-dependent anion channel (VDAC) and cardiolipin probably represent the minimum MPTP configuration [1315]. Once integrated, MPTP opening is favored by Ca 2+ accumulation in the matrix or by inhibiting the ADP/ATP translocase activity with the specific inhibitor carboxyatractyloside (CAT) [16].…”
Section: Hypothyroidism and Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation